Penyuluhan Kesehatan Reproduksi bagi Remaja Wanita di Madrasah Tsanawiyah Negeri 2 Solok - Amelia, Rizki; Delfita, Netti (Indonesian Journal of Emerging Trends in Community Empowerment, 2023)
Adolescence is a critical phase of human development marked by physical, psychological, and social changes. Accurate knowledge of reproductive health is essential to help adolescent girls navigate puberty in a healthy and responsible manner. This community service program aimed to improve the reproductive health awareness of female students at MTsN 2 Solok through educational and interactive counseling. The implementation methods included lectures, group discussions, simulations, as well as pre-tests and post-tests. The results showed a significant increase in participants’ understanding after the session, from 35% to 82% scoring above 70. Additionally, participants demonstrated high enthusiasm and active involvement throughout the activities. This program proved effective in equipping adolescents with essential knowledge and skills to maintain reproductive health and encouraged madrasah institutions to support more comprehensive and value-based health education.